Peregrine Falcon’s Dive: Pullout Maneuver and Flight Control Through Wing Morphing - Selim, Omar; Gowree, Erwin Ricky; Lagemann, Christian; Talboys, Edward; Jagadeesh, Chetan; Brücker, Christoph (AIAA Journal, 2021)
During the pullout maneuver, peregrine falcons were observed to adopt a succession of specific flight configurations that are thought to offer an aerodynamic advantage over aerial prey. Analysis of the flight trajectory of a falcon in a controlled environment shows it experiencing load factors up to 3g, and further predictions suggest this could be increased up to almost 10g during high-speed pullout. This can be attributed to the high maneuverability promoted by lift-generating vortical structures over the wing. Wind-tunnel experiments on life-sized models in the different configurations together with high-fidelity computational fluid dynamics simulations (large-eddy simulations) show that deploying the hand wing in a pullout creates extra vortex lift, which is similar to that of combat aircraft with delta wings. The aerodynamic forces and the position of the aerodynamic center were calculated from the simulations of the flow around the different configurations. This allowed for an analysis of the longitudinal static stability in the early pullout phase, confirming that the falcon is flying unstably in pitch with a positive slope in the pitching moment and a trim angle of attack of about 5 deg, which is possibly to maximize responsiveness. The hand wings/primaries were seen to contribute to the augmented stability, acting as “elevons” would on a tailless blended-wing/body aircraft.